Factors Influencing Willingness to Communicate in Classroom: EFL Students’ Voices - Syukri, Suhartini; Adam, Rikki Ramadhan; Safei, Nur Hasanah (IAIN KENDARI, 2025)
This study elaborates EFL students’ perceptions toward factors that affect their WTC in the classroom. This qualitative research applied a survey study by qualitative research utilizing 28 close ended questions and an open-ended question to elaborate on 33 participants’ voices toward factors influencing their willingness to communicate in EFL classroom instructed by native teacher. This study revealed that several factors emerge as factors influencing students’ WTC. Psychological variables such as L2 self-confidence, perceived communicative purpose, L2 learning anxiety, L2 learning motivation and situational variables such as effect of task type, topic, teacher’s role, and classroom atmosphere are contributed in raising students’ WTC in the classroom. The implication of this study pedagogically is better for the lecturers of university in reflecting the concept of teaching to scaffold students’ WTC for better learning and communication in English.